Formation pathways of PCDD/Fs during the Co-combustion of municipal solid waste and coal. (October 2018) - Chen, Zhiliang; Lin, Xiaoqing; Lu, Shengyong; Li, Xiaodong; Qiu, Qili; Wu, Angjian; Ding, Jiamin; Yan, Jianhua
Abstract: The co-combustion of simulated municipal solid waste (SMSW) and the coal in a drop-tube furnace is studied in five test cases. The concentration and signature evolution of polychlorinated dibenzo- p -dioxins (PCDD) and -furans (PCDF) in both flue gases and fly ashes are monitored at the level of individual congeners, using statistical methods. Special attention is paid to chlorophenol (CP)-route congeners, 2, 3, 7, 8-substitution, and 1, 9-substitution, to reveal the formation pathways of PCDD/Fs and the interaction between SMSW and coal. It is identified that the increase of SMSW proportion alters the major formation pathways from CP-route to chlorophenols/chlorobenzenes condensation and de novo synthesis. The coal-induced carbon enhances the adsorption capacity of fly ash particles for PCDD/Fs, yet facilitates the generation of carbon matrixes and polycyclic aromatic hydrocarbons, both of which will significantly boost the de novo synthesis with the increase of SMSW-induced chlorine and catalytic metals. Further investigations about restricting the participation of chlorine in PCDD/Fs synthesis are essential to increase the treatment capacity of MSW and to reduce the PCDD/Fs emission. Highlights: Increasing SMSW proportion alters the major formation pathways from CP-route to CP/CB condensation and de novo synthesis. The coal-induced carbon facilitates the generation of carbon matrixes and polycyclic aromatic hydrocarbons. The increase of SMSW-induced chlorine and catalytic metals significantly boost the de novo synthesis.